Pathophysiology and Management of Acute Respiratory Distress Syndrome in Obese Patients - Umbrello, Michele; Fumagalli, Jacopo; Pesenti, Antonio; Chiumello, Davide (Seminars in Respiratory and Critical Care Medicine, 2019)
A rising prevalence of obesity is reported over time and throughout the world. At the same time, the acute respiratory distress syndrome (ARDS) remains an important public health problem, accounting for approximately 10% of intensive care unit admissions and leading to significant hospital mortality. Even in the absence of acute illnesses, obesity affects respiratory mechanics and gas exchange in the setting of a restrictive disease. In the presence of ARDS, obesity adds various challenges to a safe and effective management of respiratory support. Difficult airway management, altered lung and chest wall physiology, and positional gas trapping are routinely encountered. The management of such difficult cases is generally empiric, as it is based on small-sized, physiologic studies or on suggestions from the general anesthesia literature. The present review focuses on those cases in which ARDS is coincident with obesity, with the aim of presenting treatment options based on the current evidence. The first part summarizes the epidemiology of obesity and ARDS. Then the diagnostic challenges due to obesity-related artifacts of the different imaging techniques will be presented. A subsequent, detailed description of the altered respiratory anatomy and physiology of obesity will provide help in selecting an optimal, individually tailored strategy of support. Furthermore, we will discuss how esophageal manometry should be used to adjust the settings of positive end-expiratory pressure and tidal volume; the challenges of prone positioning and extracorporeal support; and the optimal strategies for weaning from mechanical ventilation, including when and how to perform a tracheostomy.
Keywords: ARDS; obesity; mechanical ventilation